A Radiologist’s Analysis in Comparing the Diagnostic Efficacy of CT and MRI for Staging of Paediatric Renal Tumours— A Report from a Tertiary Care Hospital - Datta, Debarpita; Dakshit, Debashis; Maity, Arup (Medical Research and Its Applications Vol. 3, 2024)
Background and Objective: Approximately 7% of all paediatric malignant tumors are renal tumors [1]. Most of these are Wilms tumors or nephroblastomas. Less than 10% of primary renal neoplasms and less than 1% of all paediatric cancers are non-Wilms tumors, which include renal cell carcinoma (RCC), clear cell sarcoma, malignant rhabdoid tumour, malignant cystic nephroma, mesoblastic nephroma, and renal medullary carcinoma [2]. This is a very diverse set of malignancies, with each having a unique prognosis, treatment regimen, and relationship to genetic predispositions. In order to treat these uncommon tumors, diagnosis and staging is crucial. Even while every tumour exhibits unique radiologic characteristics, there is a significant amount of overlap. As a result, imaging like computed tomography and magnetic resonance imaging may be crucial for making the right diagnosis and prescribing the right course of action. However, the two modalities have different advantages and disadvantages in the staging of renal tumours. The objective of the study is to compare the diagnostic performance of CT and MRI for the local staging of paediatric renal tumours. Materials and Methods: The study population was derived from our hospital Medical College Kolkata and Hospital. Baseline abdominal imaging was performed with both CT and MRI.A retrospective review was done with 50 renal tumour cases selected and planned for nephrectomy over a study period of one year from October 2022 to November 2023. Each case was evaluated for capsular penetration, lymph node metastasis, tumour thrombus, preoperative tumour rupture, and synchronous contralateral lesions. The surgical and pathological findings were the reference gold standard. Results: The sensitivity of CT and MRI for detecting capsular penetration was 70% and 60%, respectively (P=0.73), while specificity was 84.3% and 84% (P=1.0). The sensitivity of CT and MRI for detecting lymph node metastasis was 80% and 53% (P=0.22), and specificity was 88% and 92% (P=1.0). Synchronous contralateral lesions were identified by CT in 5/12 cases and by MRI in 8/12 cases. Conclusion: CT and MRI have similar diagnostic performance for detection of lymph node metastasis and capsular penetration. MRI was more accurate in detecting contralateral synchronous lesions. Hence either modality can be used for initial loco–regional staging of paediatric renal tumours.